What are the real effects of financial market liquidity? Evidence on bank lending from the euro area - Andreas R. Dombret; Daniel Foos; Kamil Pliszka; Alexander Schulz (Deutsche Bundesbank, 2018)
We analyze the impact of market liquidity on bank lending in the euro area for different segments over the period 2003 to 2016. Our results on the aggregate level show that market liquidity is positively related to loan volumes and negatively related to credit spreads. Particularly during the financial crisis of 2007-09 and the subsequent European debt crisis, lending was reduced and we observe that banks requested higher credit spreads. Of particular importance is that market liquidity has an asymmetric effect on bank lending: The negative impact of a reduction in liquidity is more significant than the positive impact of an increase in liquidity. This is particularly true for corporate loans where lending conditions would be restricted first in times of impaired market liquidity. The bank-level data confirm the strong impact of market liquidity on bank lending as well. More specifically, we show that non-listed banks, less profitable banks and banks which rely relatively more on net interest income, as well as banks with a high funding liquidity are particularly strongly exposed to market liquidity. Therefore, properly functioning and sufficiently liquid markets are necessary to avoid negative consequences of restrictions in bank lending which would eventually hamper the real economy. This is of the utmost importance against the background of the envisaged capital markets union in the European Union and the potential exit of the United Kingdom from the EU.
Keywords: G15; G21; G32; 330; financial markets; bank lending; liquidity risk